African Big Economies on the Continental Trade Liberalisation and Migration Policy Development - Enaifoghe, Andrew Osehi; Maduku, Harris (Journal of Economics and Behavioral Studies, 2019)
African countries are faced with a broad spectrum of political and economic challenges that have shadowed hugely in an anticipated socio-economic prosperity. The continent overtime has resolved to come up with a single currency as well as opening borders for trade but none of that has been realised. Polarisation of economic development has caused brain drain within the continent with educated people from poorly governed countries moving across borders (Europe and America), and the same happens with gifted entrepreneurs who search for a country with a better business enabling environment than their own home countries. There is uneven development in Africa with very poor, fragile and better performing countries constituting the continent. This has caused a huge burden on those economies that are doing well as those economies have to create jobs for immigrants as well and for their own people. However, the founding principles of the African Union were basically to bring African countries together and help each other to see through economic and political prosperity across the continent in as much as there are laid out guiding rules. Africa has continued to be a highly protective continent especially amongst itself as most countries still require visas from citizens of other African countries, while countries still impose import duties and all forms of control on imports and practices that are against the foresights of the founding principles of the African Union. This paper acknowledges the efforts that have been done in the West and South of Africa for the formation of regional blocks that desire to achieve socio-economic progress in those regions. The formation of ECOWAS in the WEST and SADC in the South are good strides towards integration efforts in Africa but if the founding objectives of the African Union are to be achieved, member countries still have to do more. This paper recommends the two biggest countries in Africa to make use of their economic power to influence smaller member states to also envision possible socio-economic benefits that can emanate from total integration of the continent. They could make use of the African parliament, African Union summits and other several platforms to lobby for this important goal.